الفجوة بين المهارات والمعارف المكتسبة من تخصص المحاسبة وبين متطلبات سوق العمل السعودي - ملو العين علاء محمد عبد الله (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت الدراسة الحالية إلى معرفة الفجوة بين المهارات والمعارف المكتسبة من تخصص المحاسبة ومتطلبات وحاجات سوق العمل السعودي بالقطاع الخاص والعام. وشمل التحليل الجوانب النظرية والتطبيقية من خلال المسح المكتبي لأدبيات هذا الموضوع والمسح الميداني لآراء عينة من خريجي الكليات التقانية في تخصص المحاسبة وأصحاب العمل الذين يعمل لديهم هؤلاء الخريجون. وقد استندت الدراسة على عدد من الأساليب الإحصائية لتحليل استبانات العينة المستهدفة, حيث توصلت الدراسة إلى عدد من النتائج الهامة كان من أهمها أن هناك فروقات ذات دلالة إحصائية بين المهارات والمعارف المكتسبة لدى خريجين تخصص المحاسبة وبين متطلبات سوق العمل السعودي بقطاعيه الخاص والعام, هناك فروقات ذات دلالة إحصائية في العوامل المؤثرة في توظيف خريجو تخصص المحاسبة وذلك من وجهة نظر الخريجين وأصحاب العمل, وأخيرا هناك فروقات ذات دلالة إحصائية في مستوى الكفاءة المهنية بين خريجو الكليات التقنية وخريجو المؤسسات التعليمية الأخرى في تخصص المحاسبة. The present study aims to find out the gap between acquired skills and knowledge of Accounting field and the requirements of Saudi Labour Market for both private and public sector. The analysis included the theoretical and practical sides through official scanning of literatures concerning this subject and a sample that has been drawn up consisting graduates in Accounting from Technical Colleges and their employers. The study relied on a number of statistical techniques to analyze the responses of the targeted sample. The main findings of the present study can be summarized as follows: there are significant differences with statistical reference between skills and knowledge gained from Accounting program and requirements of Saudi labor market both private and public, there are also significant differences in those factors that influence employing Accounting graduates from the point of view of graduates and employers, and finally, there are significant differences also with statistical references in the level of professional efficiency between graduates of technical colleges and other educational institutions in Accounting programs .